When the old guys knew better: The true identity of Mimosa longepedunculata and reestablishment of M. tocantina (Leguminosae, Mimosoideae) - Borges, Leonardo Maurici; Pirani, José Rubens (Phytotaxa, 2014)
Megadiverse genera usually have a complex taxonomy. One factor influencing this complexity is concerned to synonyms, which are often numerous in widespread and morphologically variable species. In this article we examined the case of Mimosa longepedunculata and M. tocantina, two sympatric narrowly distributed species from central Brazil, considered to be synonyms in Barneby’s monograph. We show that this was an inaccurate taxonomic decision related to a misinterpretation of the type specimens and, possibly, also to sampling biases in field works. The definition of each species is here clarified and M. tocantina is reestablished and considered a distinct species from M. longepedunculata, having M. pseudosetosa as a new synonym. A regional identification key for the species is provided together with data on distribution and habitat, flowering and fruiting, conservation status, etymology, and notes on morphology. Illustrations, pictures and a full description of M. longepedunculata are also presented.